TEST OF CRITICAL THINKING ABILITY ASSEMBLY ASSESSMENT PROTOTYPE - Erna Juita; Dasrizal Dasrizal; Elvi Zuriyani (Universitas Sebelas Maret (UNS), 2022)
The purpose of this study is to develop and implement and produce valid and practical assessment tools for critical thinking skills in disaster geography learning. Assessment tools are said to be valid if they have been declared appropriate to be used to measure the process and learning outcomes of disaster geography by geography education experts and education evaluation experts. In the research design this development follows the development model according to plomp which consists of three phases. In this study only took the prototyping phase (prototype phase). The instrument used in this study is an assessment that has been designed beforehand in the form of selfassessment assessment, assessment of colleagues and critical thinking assessment. After the device was made, three trials were conducted which consisted of one-on-one (individual) trials, small group trials, and large group trials. The results obtained in this study are limited to the results of trials in small groups by evaluating previously designed assessments